Optic Nerve Disorders Diagnosis and Management - Chan, Jane W. (Springer New York : Imprint: Springer, 2014)
Optic Nerve Disorders: Diagnosis and Management, Second Edition, is a thoroughly revised and updated reference, including new information on diagnostic techniques such as genetic testing for hereditary optic neuropathies, new data on toxic/drug-related optic neuropathies, and recent data from clinical trial studies. Additional novel therapies, including stem cell therapies, the use of nanotechnology, and gene therapies are featured highlights, as is spectral domain optical coherence tomography (OCT) for imaging of the optic nerve. The way in which OCT is used in differentiating optic nerve disorders from other retinal disorders, and how OCT is used in monitoring the course of the disease, is also discussed. This practical reference focuses on common optic nerve disorders. It addresses diagnosis, pathophysiology, management, and prognosis, and is written in a clear, concise style for quick, easy reference in the clinic. With additional color photographs to better illustrate the material, the second edition will prove to be the go-to reference for ophthalmologists, neurologists, and neurosurgeons working with optic nerve disorders.